2018
DOI: 10.1007/s00213-018-5031-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased amygdalar metabotropic glutamate receptor 7 mRNA in a genetic mouse model of impaired fear extinction

Abstract: These data show altered mGlu receptor expression in key brain regions associated with fear extinction in two different inbred mouse strains which differ markedly in their fear extinction behaviour. Altered mGlu receptor levels may contribute to the deficit fear extinction processes seen in fear extinction in the S1 strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The exploitation of NMDARs may be further complicated not only by sex differences in the mechanisms underlying extinction, but also by the interaction between female reproductive history and the requirement for NMDARs in extinction reported by Tang and Graham (2019). Thus, a complex constellation of factors may contribute to individual differences in receptor expression, such as those described by O’Connor et al (2019) for metabotropic glutamate receptors, and consequent differences in fear extinction.…”
Section: New Mechanistic Insights Into the Psychopharmacology Of Extimentioning
confidence: 99%
“…The exploitation of NMDARs may be further complicated not only by sex differences in the mechanisms underlying extinction, but also by the interaction between female reproductive history and the requirement for NMDARs in extinction reported by Tang and Graham (2019). Thus, a complex constellation of factors may contribute to individual differences in receptor expression, such as those described by O’Connor et al (2019) for metabotropic glutamate receptors, and consequent differences in fear extinction.…”
Section: New Mechanistic Insights Into the Psychopharmacology Of Extimentioning
confidence: 99%
“…Individuals with ASD are at an additional risk for developing anxiety (Perihan et al, 2020). A growing body of studies has supported the notion that mGluR7 has a dominant role in anxiety role (Kotlinska et al, 2019;O'Connor et al, 2019). Data with AMN082 would suggest the use of mGluR7 receptor agonists for treating anxiety (Spooren et al, 2010;Cieślik et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Metabotropic glutamate receptors expressions are (mGlu) associated with fear extinction process. The increased expression of mGlu7 is associated with deficits in the fear extinction process in PTSD ( O’Connor et al, 2019 ). Another study reported that increased mGlu5 mRNA expression in the BLA, IL-PFC, and PL-PFC contributes to stress-resilient behavior after traumatic stress ( Shallcross et al, 2021 ).…”
Section: Molecular Mechanisms Affecting the Fear Circuitry In Ptsdmentioning
confidence: 99%
“…Increase the susceptibility of mice to PTSD-like behavior (Lebow et al, 2012) Increase expression of mGlu7 Deficits in fear extinction process (O'Connor et al, 2019) CPEB3 (cytoplasmic polyadenylation elementbinding protein 3)…”
Section: Genetic and Epigenetic Regulationmentioning
confidence: 99%